Morphological Variations and Morphometric Analysis of Foramen Ovale in South Indian Population - Supriya Garapati; Ariyanachi Kaliappan; Subhashini Rani Vuba; Ravi teja; Kishore Yadav Punnapa; Bollavaram Pullanna (International Journal of Human Anatomy, 2024)
Introduction The foramen ovale is located in the area where intracranial and extracranial structures meet. Procedures involving trigeminal neuralgia and mandibular nerve anaesthesia require an understanding of the foramen ovale's morphometry and anatomy. Our present study was conducted to define mean values and anatomical variations in foramen ovale. Aims 1. To establish the mean length, breadth and the Area of the foramen ovale. 2. And also to study different shapes and special features of the foramen ovale. 3. To compare the values of the present author with the previous studies. Methodology The study was carried out on100 foramen ovale using 50 dry adult human skull bones of unknown sex. Maximum transverse diameter, antero-posterior diameters of the foramen were measured with the help of vernier calipers. and the different shapes of foramen were noted. The data was analysed by using unpaired T test. Results The mean anteroposterior diameter on left side was 6.59±1.37 mm and on right side was 6.99±1.44 mm. The mean transverse diameter on the left is 4.09±0.74 mm and 4.17±0.76 mm on the right side. Incidences of various shapes of the foramen ovale were oval 70%, almond 11%, round 9%, elongated 6%, pear shaped 2 % and irregular 2%. Conclusions The findings from the current study may be useful for understanding the variations of these foramina for interventions in middle cranial fossa.
Keywords: Foramen ovale